Heat Transfer Effect of Reheater Tube Materials Steam Power Plant - M Prihajatno (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2015)
Reheater tube is an installation for steam reheating output of turbine to work encouraging. Therefore need be heated again of steam to increase pressure and temperature so be used for drive turbine blades. Reheater tube last work for 54,000 hours. The method used of study to mechanical test and visual and microstructure observations. It is also used iterative method for temperature loads calculation occur in reheater tube. The result of iterative calculation obtained wall tube temperature T1 = 608.43 °C, T2 = 618.18 °C, T3 = 655.74 °C and convection coefficient = 3.604,37 W/m2.oC. Based on mechanical strength of materials tube is 481.85 MPa, this is still above the minimum standards of material SA-213 T22 so that decrease was not significant. Visual observation accour oxidation corrosion and visible cavity in micro structure. Some spheroidized and decarburizing phenomena are also seen in microstructure materials. The phenomenon is due to high temperature and pressure at the long term.